Extracting and Evolving a Software Product Line from Existing Web-based Systems: An Experience Report - de Pontes, Erick Sharlls Ramos; Kulesza, Uirá; da Silva, Carlos Eduardo; Adachi, Eiji; Cirilo, Elder R. (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
This paper presents an experience report of extraction and evolution of software product lines (SPLs) from existing web-based systems. We describe the activities to succesfully refactor and evolve an web-based system of management of university rooms and laboratories by promoting the management and modularization of their variabilities. Several lessons learned are derived from that experience, includying the proposal of a method for the extraction and evolution of SPLs, as well as strategies for variability refactoring.